Analysis of Obesity and Differences in Nutritional Status of School Children in Central and Southern Region of Montenegro - Dragan Bacovic (Journal of Anthropology of Sport and Physical Education, 2020)
The aim of this research was to deteremine obesity and differences in nutritional status of school children in Central and Southern region in Montenegro. The research involved 189 children divided into two sub-samples: 84 children (7-8 years) from Central region and 105 children (7-8) years from Southern region of Montenegro. Anthropometrics characteristics were evaluated by a battery of 3 variables: body height, body weight, waist circumference. Mentioned variables were used to calculate following anthropometric indexes which gave as informations about obesity: body mass index (BMI), waist to height ratio (WHtR). The difference between the children are tested by a t-test for small indenpendent samples. It’s determined that there are no significant differences between children in Central and Southern region of Montenegro in any monitored variables. Also, it was found that 16.4 % of children were obese and those results can help us to aprehend problem of excessive body weight at specified age and find adequate solutions for this problem.